Compact wide single‐/dual‐band bandpass filter with equal inductance configuration in thin film IPD technology - Liu, Zhi‐Hao; Liu, Bao‐Guang; Cheng, Chong‐Hu; Cheng, Yong (Electronics letters, 2024)
Here, based on thin film integrated passive device (TF‐IPD) technology, compact ultra‐wideband (UWB) bandpass filter (BPF) and dual‐band bandpass filter (DBBPF) with equal inductance configuration are proposed. The configuration of equal inductance in a circuit contributes to reducing variables, simplifying the physical structure, and shortening the debugging time in the TF‐IPD design process. Despite all the inductors being equal in value, a wide passband can still be achieved. The measured results show that the centre frequency of UBW BPF is 11.43 GHz, and the 3‐dB fractional bandwidth (FBW) is 133% (3.87–18.99 GHz). And the 3‐dB FBWs of DBBPF centred at 6.5 GHz and 16.2 GHz are 92% (3.51–9.49 GHz) and 35% (13.33–18.98 GHz), respectively. The stopband of UBW BPF and DBBPF can be extended to 47.7 GHz and 44.8 GHz in sizes of 321 µm × 856 µm and 235 µm × 846 µm, respectively (excluding measuring pads). In this paper, compact ultra‐wideband (UWB) bandpass filter (BPF) and dual‐band bandpass filter (DBBPF) with equal inductance configuration are designed. This kind of filter with equal inductance is helpful to reduce the variable, simplify the physical structure and shorten the debugging period. Even if all inductance values are equal, wide passband can still be achieved.